고객의 효율적인 쇼핑을 위한 RFID/USN 기반 이동형리더기를 이용한 u-마트 네트워크 - 조건화(Jianhua Diao); 양진호(Jin-Ho Yang); 안병태(Byeong-Tae Ahn); 강현석(Hyun-Syug Kang) (한국콘텐츠학회 논문지, 8(5), 2008)
RFID/USN is considered important basic infra of ubiquitous community and tried practical adaption through various research. Specially, there is during researcher progresses for stock and state management of logistics to let you get at u-mart systems. It discern thing from warehouse to deliver as adhere RFID tag of palette in keeping unit of article and construct form of thing to analyze information of environment status using sence module based on function of wireless communication. in the paper, propose composition of customer satisfaction system using RFID chip in u-Mart status management system based on RFID/USN and according to analysis specific information of commodity, propose movement reader device to offer real-time information from customer. And it presents the improvement program for the provision of product information which is appropriate uses the RFID chip and the provision of control information in the customer who is a core of consuming. RFID/USN은 유비쿼터스 사회의 중요한 기반 인프라로서 고려되며 다양한 연구를 통해 실용적인 접목이 시도되고 있다. 특히 u-마트 시스템에서 물류의 입출 재고와 상태 관리를 위한 연구가 진행 중에 있다. 이는 물품 보관 단위인 파렛트에 RFID 태그를 부착하여 입.출고 시의 물품을 식별하고 무선 통신기능을 가진 센서 모듈에 의해 환경 상태 정보를 파악하는 물품의 형태로 이루어진다. 본 논문에서는 RFID/USN 기반의 u-마트 상태 관리 시스템에서 RFID 칩을 이용한 고객 만족 시스템 구성을 제안하고 상품의 상세한 정보를 파악하여 고객에게 실시간으로 정보를 제공하는 이동형 리더기를 제안한다. 그리고 소비의 주체인 고객에게 RFID 칩을 이용한 적절한 제품 정보의 제공과 제어 정보의 제공을 위한 개선 방안을 제안한다.